Regulated upon activation, normal T cell expressed and secreted (RANTES) levels in the peripheral blood of patients with Alzheimer's disease - Vacinova, Gabriela; Vejražkova, Daniela; Rusina, Robert; Holmerová, Iva; Vaňková, Hana; Jarolímová, Eva; Včelák, Josef; Bendlová, Běla; Vaňková, Markéta (Neural regeneration research, 2021)
Alzheimer's disease (AD) is the most common type of dementia, but it is very difficult to diagnose with certainty, so many AD studies have attempted to find early and relevant diagnostic markers. Regulated upon activation, normal T cell expressed and secreted (RANTES, also known as C-C chemokine ligand) is a chemokine involved in the migration of T cells and other lymphoid cells. Changes in RANTES levels and its expression in blood or in cerebrospinal fluid have been reported in some neurodegenerative diseases, such as Parkinson's disease and multiple sclerosis, but also in metabolic diseases in which inflammation plays a role. The aim of this observational study was to assess RANTES levels in peripheral blood as clinical indicators of AD. Plasma levels of RANTES were investigated in 85 AD patients in a relatively early phase of AD (median 8.5 months after diagnosis; 39 men and 46 women; average age 75.7 years), and in 78 control subjects (24 men and 54 women; average age 66 years). We found much higher plasma levels of RANTES in AD patients compared to controls. A negative correlation of RANTES levels with age, disease duration, Fazekas scale score, and the medial temporal lobe atrophy (MTA) score (Scheltens's scale) was found in AD patients, i.e., the higher levels corresponded to earlier stages of the disease. Plasma RANTES levels were not correlated with cognitive scores. In AD patients, RANTES levels were positively correlated with the levels of pro-inflammatory cytokines interleukin-6 and tumor necrosis factor-α, which is consistent with the well-known fact that AD is associated with inflammatory processes. RANTES levels were also positively correlated with insulin levels in AD patients, with insulin resistance (HOMA-R) and pancreatic beta cell function (HOMA-F). This study evaluated several clinical and metabolic factors that may affect plasma levels of RANTES, but these factors could not explain the increases in RANTES levels observed in AD patients. Plasma levels of RANTES appear to be an interesting peripheral marker for early stages of AD. The study was approved by the Ethics Committee of Institute of Endocrinology, Prague, Czech Republic on July 22, 2011.